Meta-analysis: Resistance Training Improves Cognition in Mild Cognitive Impairment - Zhang, Lulu; Li, Bin; Yang, Jingjing; Wang, Fengling; Tang, Qianyun; Wang, Shuhong (International Journal of Sports Medicine, 2020)
This study investigated the benefits of resistance training on cognition in patients with mild cognitive impairment. We searched the PubMed, Embase and Cochrane Library databases, and seven randomized controlled trials were reviewed. We evaluated the risk of bias using the Cochrane Collaboration’s bias assessment tool. Standard mean differences with 95% confidence intervals were calculated for statistical analysis. This meta-analysis assessed three variables: general cognitive function, executive function and working memory. The results indicate that general cognitive function improved significantly (standardized mean difference: 0.53, P=0.04), and further subgroup analyses on frequency and duration per session showed that the subgroups ‘twice a week’ (P=0.01) and ‘duration per session >60 min’ (P=0.0006) exhibited better performance than the subgroups ‘three time a week’ (P=0.47) and ‘duration per session <60 min’ (P=0.53). Additionally, a moderate effect size was found in executive function (standardized mean difference: 0.50, P=0.0003), and there was non-significant effect in working memory (P=0.14). In summary, resistance training may mitigate mild cognitive impairment by improving cognition. Larger-scale studies are recommended to demonstrate the relationship between resistance training and cognition in mild cognitive impairment.
Keywords: exercise therapy; cognitive dysfunction; mild cognitive impairment; randomized controlled trials as topic; meta-analysis